2015
DOI: 10.1002/bip.22584
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate‐binding module tribes

Abstract: At present, 69 families of carbohydrate-binding modules (CBMs) have been isolated by statistically significant differences in the amino acid sequences (primary structures) of their members, with most members of different families showing little if any homology. On the other hand, members of the same family have primary and tertiary (three-dimensional) structures that can be computationally aligned, suggesting that they are descended from common protein ancestors. Members of the large majority of CBM families a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Support for homology also comes from the similar and unusual ability to induce plant cell wall creep without lytic activity. Moreover, although many classes of CBM have a β-sandwich fold, the specific β-strand arrangement of D2 appears to be unique and is not shared with other CBMs (Carvalho et al 2014). Shoseyov et al (2006) reported that expansin D2 resembles the fold of CBM family 3, but our structural comparison as well as that of Carvalho et al (2014) indicate that D2 has a distinct β-strand arrangement, which makes homology with CBM3 unlikely.…”
Section: Phylogenetic Distribution and Evolution Of Bacterial And Othmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for homology also comes from the similar and unusual ability to induce plant cell wall creep without lytic activity. Moreover, although many classes of CBM have a β-sandwich fold, the specific β-strand arrangement of D2 appears to be unique and is not shared with other CBMs (Carvalho et al 2014). Shoseyov et al (2006) reported that expansin D2 resembles the fold of CBM family 3, but our structural comparison as well as that of Carvalho et al (2014) indicate that D2 has a distinct β-strand arrangement, which makes homology with CBM3 unlikely.…”
Section: Phylogenetic Distribution and Evolution Of Bacterial And Othmentioning
confidence: 99%
“…Moreover, although many classes of CBM have a β-sandwich fold, the specific β-strand arrangement of D2 appears to be unique and is not shared with other CBMs (Carvalho et al 2014). Shoseyov et al (2006) reported that expansin D2 resembles the fold of CBM family 3, but our structural comparison as well as that of Carvalho et al (2014) indicate that D2 has a distinct β-strand arrangement, which makes homology with CBM3 unlikely. Expansin domain D2 is now classified as CBM family 63 in the CAZY.ORG database (Georgelis et al 2012).…”
Section: Phylogenetic Distribution and Evolution Of Bacterial And Othmentioning
confidence: 99%
“…In the Carbohydrate Active enZymes (CAZy) database (; http://www.cazy.org/), the SBDs have been classified among the families of carbohydrate‐binding modules (CBMs). Currently, there are 83 different CBM families with 15 considered SBDs due to their ability to bind starch and related α‐glucans, such as glycogen, cyclodextrins and various maltooligosaccharides – these are CBM20, CBM21, CBM25, CBM26, CBM34, CBM41, CBM45, CBM48, CBM53, CBM58, CBM68, CBM69, CBM74, CBM82 and CBM83 . The CBM74 members are about 250 residues long and this family obviously represents a novel type of an SBD .…”
mentioning
confidence: 99%
“…In general, an SBD is a protein module consisting of ∼100 amino acid residues and containing aromatic residues at certain positions (mostly tryptophans and tyrosines, but also phenylalanines or histidines) that are essential for the SBD to bind carbohydrate, that is, raw starch and/or related α‐glucans, and thus enhance the degradative action of the enzyme to which the SBD is attached . It is of note that raw‐starch degrading amylases without any distinct SBD exist and are also well known .…”
Section: Introductionmentioning
confidence: 99%